ACCESSIBILITY AND INFLUENCER MARKETING STRATEGIES ON SALES GROWTH THROUGH BANKING GUARANTEES UMKM IN MEDAN CITY - Bunga Aditi (CV. Radja Publika, 2024)
The main indicators that make MSMEs experience many losses to the point of bankruptcy, including consumer demand for the product is decreasing, then the regulations and policies issued by the government do not provide direct benefits in developing MSMEs so that they are not felt directly by the community, especially Micro, Small and Medium Enterprises (MSMEs) who have to close for a long time. The purpose of this studyreviewing and analyzing Online Marketing Strategies and Banking Guarantees in Reducing Bankruptcy of MSMEs in Medan City.This study uses a data analysis method using SmartPLS software. The results of the study showAccessibilitysignificant effect on banking guarantees. Banking guarantees have a significant effect on sales growth. Banking guarantees as an intervening variable have a significant impact on increasing the influence of Accessibility on sales growth.